In situ atomically dispersed Fe doped metal-organic framework on reduced graphene oxide as bifunctional electrocatalyst for Zn–air batteries. Issue 34 (4th August 2021) - Zhao, Xiaolin; Shao, Lin; Wang, Ziming; Chen, Huibing; Yang, Haipeng; Zeng, Lin
Abstract : A porous atomically dispersed Fe doped ZIF-8-derived nanocatalyst has been successfully grown on reduced graphene oxide (rGO), and the optimal Fe–N–C/2rGO catalyst exhibited an excellent bifunctional performance for Zn–air batteries. Abstract : It is an urgent and pressing demand to replace the traditional noble metal catalysts for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) of Zn–air batteries. The non-precious metal catalysts exhibit a great promise for high electrocatalytic activity. Herein, we develop a simple strategy to prepare a porous atomically dispersed Fe doped ZIF-8-derived nanocatalyst supported on reduced graphene oxide (rGO). The optimal Fe–N–C/2rGO catalyst with a sandwich-like structure is constructed by a uniform Fe-doped ZIF-8 carbon particle layer covering the rGO surface, which demonstrates an excellent performance for ORR with a half-wave potential E 1/2 of 0.88 V vs. RHE and OER with a voltage of 1.56 V at 10 mA cm −2, compared with that of commercial Pt/C ( E 1/2 = 0.86 V) and IrO2 (1.62 V at 10 mA cm −2 ) in 0.1 M KOH, respectively. The ingenious construction prevents the Fe-doped ZIF-8 particles and rGO from the agglomeration. It enables a rechargeable Zn–air battery with a high peak power density of 164 mW cm −2 and excellent cycling stability. This approach provides a convenient path for constructing and designing highly active catalysts for the Zn–air batteries.